Individual death and collective life in Spinoza - Merçon, Juliana (Cadernos Espinosanos, 2010)
This article discusses three basic questions. Firstly, we ask: Why would freedom of thought and expression be a necessary condition for social peace? Spinoza’s answers will assist us in understanding the serious political mistake of condemning those who confront the established regime to exile, prison or death. Among the rare cases of individuals who reaffirm their honesty when this attitude implies a risk of death, we will select Socrates’. The alleged words of this legendary philosopher will lead us to a second discussion: Can reason determine one to act honestly even when that implies one’s own death? Would not reason thus oppose conatus? Finally, from considerations about the bonds between individuality and collectivity, ethics and politics, the last question will emerge: How are love of self, love of others and love of Nature related?